Photoelectric Detection of Nitrogen‐Vacancy Centers Magnetic Resonances in Diamond: Role of Charge Exchanges with Other Optoelectrically Active Defects. Issue 5 (17th March 2022) - Bourgeois, Emilie; Soucek, Josef; Hruby, Jaroslav; Gulka, Michal; Nesladek, Milos
Abstract: The photoelectric detection of nitrogen‐vacancy (NV) magnetic resonance (PDMR) in diamond, used for spin state detection and based on reading the photocurrent resulting from NV ionization, offers physical and technical advantages for the development of miniaturized and scalable quantum sensors, as well as solid‐state quantum information devices integrated with electronics. Charge exchanges between NV centers and other optoelectrically active defects in diamond are an essential part of the PDMR scheme, impacting the spin‐state control and the performances of the photoelectric readout. Through experimental characterization and modeling, processes governing the spin‐state contrast, in particular the hole carrier contribution to the photocurrent and the role of acceptor‐type defects are discussed. Such acceptor defects can act as traps for free electrons resulting from NV photoionization. Consequently, the hole current can increase at resonance, ultimately leading to an inversion of the sign of PDMR resonances, i.e. to a positive spin contrast. Based on these findings, a method to improve PDMR performances in terms of spin contrast and photoelectric detection rate by selectively ionizing low‐energy acceptor defects using a bias red illumination is proposed. This method is shown to lead to a significant improvement of the photoelectric spin detection sensitivity, important for future practical devices. Abstract : The photoelectric readout of nitrogen‐vacancy centers electron spin offers perspectives for the development of miniaturized, scalable diamond quantum devices. Through experiments and modelling, the strong impact of charge exchanges between NV centers and other opto‐electrically active defects on the photoelectric detection of NV spin is here demonstrated. A method to mitigate the detrimental effects of these charge exchanges is presented.